William of Tyre, Femininity, and the Problem of the Antiochene Princesses. Issue 4 (October 2019) - BUCK, ANDREW D.
Abstract : This article examines the representation of women and femininity in Archbishop William of Tyre's Chronicon . It considers how his text was shaped by contemporary Western ideas of gender, and how this impacted upon his presentation of women, especially Queen Melisende of Jerusalem and three Antiochene princesses, Alice, Constance and Sybil. It argues that, in doing so, we can raise important questions regarding his use for empirical reconstruction by revealing the nuanced ways in which, in pursuit of broader narrative goals, he utilised gender as a tool to both praise and discredit.